Financial Performance Analysis of the Jambi Province Local Government Using the Value for Money Method (2017-2024 Period) - Zelvi Tiara; Mukhzarudfa Mukhzarudfa; Eko Prasetyo (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the financial performance of the Jambi Provincial Government using the Value for Money approach, which covers the aspects of economy, efficiency, and effectiveness during the 2017–2024 period. The population of this study consists of all financial reports of the Jambi Provincial Government, while the sample is the Budget Realization Reports for the observed years, selected using a time series technique based on data availability. This research employs a quantitative approach with a descriptive research design. The data used include secondary data obtained from official budget realization reports and primary data collected through interviews conducted at the Jambi Provincial Finance and Asset Agency. Data collection techniques comprise documentation and interviews, and data analysis is carried out using economic, efficiency, and effectiveness ratios within the Value for Money framework. The results show that the financial performance of the Jambi Provincial Government during the study period is categorized as economical, as the expenditure realization ratio is below 100 percent, indicating budget savings. However, in terms of efficiency, the performance is still considered inefficient because the ratio exceeds 100 percent, which means expenditure realization is higher than revenue realization. Meanwhile, in terms of effectiveness, financial performance is classified as effective since revenue realization has met and even exceeded the predetermined targets. In conclusion, the Jambi Provincial Government has managed its budget economically and effectively, but improvements are still required to enhance efficiency in regional financial management.